The premises of the development of the private sector in Poland – some conclusions - Kozłowski, Maciej (Comparative Economic Research. Central and Eastern Europe, 2010)
Processes of transformation in companies or more broadly the economic transformation is a part if a wider process of the systemic transformation. Within this process, a special place is held by the political system, although it should be remembered that these are changes in the economic system which will ultimately determine a success or failure of occurring changes. Parallel, there must be taking place changes in the social structure. These must both consolidate new structures or force out a slowdown in the speed of occurring changes, as well as demand a restoration of old solutions. In a longer time perspective, the preserving of political power will depend on the remodeling of economic system in accordance with the assumed conception, because any significant changes in this system may pave the way for the strengthening of political system. Hence, the speed of occurring transformations plays also an important role here. All this shows that the speed of changes. in the economy must be particularly well balanced and adapted to a concrete situation. Changes in social structures will be taking place at a similar speed enlarging various groups of persons interested in transformation processes. The transformation process will be successful if the main part of the society accepts the system of values corresponding to the new social system. The success of the deep restructuring of economic relations in our economy depends primarily on the effectiveness of the reform aimed to restructuring of ownership in all sectors. This requires a new approach to the prospects of private property growth, i.e. an approach unbiased by any doctrinal prejudices, as well as suggestions glorifying private property as a panacea to cure Poland’s economy. The Polish economy is characterised both by objective and subjective premises in the development of the private sector and a strong motivation of individuals to launch their own business activities in this sector.